CONCEPTS OF SUSTAINABLE DEVELOPMENT THROUGH THE APPLICATION OF GREEN TECHNOLOGIES IN INDUSTRY (World Economics and Finance Bulletin, 2025)
The shift towards sustainable development has become a strategic priority for many countries, including developing nations like Uzbekistan. This article examines the key concepts of sustainable development in the context of industrial production, highlighting the pivotal role of green technologies. It explores how the integration of environmentally friendly technologies in industrial enterprises contributes to reducing environmental degradation, enhancing energy efficiency, and fostering long-term economic resilience. The paper analyzes global best practices and presents potential pathways for implementing sustainable industrial strategies using green innovations.